Isolation of a Nonpigmented, Thermophilic Bacterium Similar to Thermus aquaticus - Ramaley, Robert F. (1970)
A thermophilic (70 C), gram-negative bacterium has been isolated that resembles Thermus aquaticus but lacks the type-characteristic yellow carotenoid.